Sonochemical Degradation of Benzothiophene (BT) in Deionized Water, Natural Water and Sea Water - Khadijah M. Al-Zaydi; Christian Petrier; Sameera M. M. Mousally; Sana T. Arab; Moamen S. Refat (Molecules, 2019)
This paper deals with the sonochemical water treatment of polycyclic aromatic sulfur hydrocarbons (PASHs), one of the most common impurities found in waste water coming from petroleum industry. The best fit of the experimental data appears to be the kinetic parameters determined using the Michaelis-Mentonmodel in the concentrations range of the study. For the initial increase in the degradation rates, it is simply considered that the more the bulk concentration increases, the more the concentration in the interfacial region increases. This will be explained by Michaelis-Menton kinetics. The influence of organic compounds in the water matrix as a mixture with Benzothiophene (BT) was also evaluated. The results indicated that BT degradation is unaffected by the presence of bisphenol A (BPA). Finally, the results indicated that ultrasonic action is involved in oxidation rather than pyrolitic processing in the BT sonochemical degradation.